KARYA DAN PERAN K.H. HALIMY DALAM KADERISASI ULAMA BANTEN - Ayatullah Humaeni (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
This article tries to discuss the biograpfhy of KH.Halimy, his role in farming of cadres of Ulama in Ciomas Banten, and his work. This article is a result of field research using descriptive qualitative method based on hisoticaf and anthropological approaches. Literature study, obseroation, interview and documentation are used to collect the data of the research. The data was, then, analyzed by using biographical analysis. As an ulama who was born among the society whose coarse image and was well-k nown as the center of the jawara (local strongman) of Banten, KH. Halimy emerged as a local ulama who had well behaved attitude, but hard hitting and high discipline who taught his society to be brave not only phisically, but also intellectually and morally. As a result, from his pesantren, it has been born many kyai who were not only able to transfer as well as to teach what had been taught by KH. Halimy, but also able to establish a pesantren in their origin villages. KH.Halimy was a charismatic kyai who had important role in farming religious values through religious teaching in the pesantren Al-Halimy and to Ciomas Banten society.Religious traditions that was inherited to Ciomas society such as reciting Sura yaa-sin, marhaban, dalail, and reading the book of dardir conducted regularly was still maintained by the Ciomas society up to the present day, and it becomes a religious activity that functions not only as a farm of religious service to the God, but also as a symbol of equality and social solidarty of Ciomas society. Key Words: Ulama, KH. Halimy, Ciomas, Banten